Independent directors and profitability: Evidence from Indonesia - Erfan Rachmadi; Bimo Saktiawan (Sebelas Maret Business Review, 2024)
The primary response to this issue was to introduce and strengthen the role of independent directors in the board of directors. Independent directors aim to improve the quality of corporate governance by ensuring adequate management supervision so that stakeholders and shareholders can be well looked after. This article examines independent directors' influence on company profitability in Indonesia. The data used in this research comes from 90 companies in Indonesia from 2013 to 2022. We use panel data regression analysis as a method to measure the influence of independent directors on profitability. We find that independent directors have a significant favorable influence on company profitability. These findings support the hypothesis that the presence of independent directors can improve company performance through effective monitoring and objective decision-making. In addition, these results show that good corporate governance practices, namely practices involving independent directors, are an essential factor in increasing company profitability in Indonesia.